Independent Palm Oil Small Holders' Plans Regarding Their Behaviour - Reza Winata Aulia Hutami; Said Muhammad Ikhsan Zulfi Maaruf; M. Ramli; Mulono Apriyanto (Akademi Komunitas Perkebunan Yogyakarta, 2023)
The ISPO (Indonesian Sustainable Palm Oil) framework, which describes best practises for the production of ecologically friendly oil palm plantations, absolutely has to be put into reality. This is of the utmost importance. This study aims to analyse the behavioural intentions of independent small holders located within the Riau Regency in regard to extending their sustainable palm oil enterprises. Specifically, this research will look at how these individuals plan to grow their palm oil operations. Throughout the course of this investigation, structural equation modelling was utilised as a tool for doing both descriptive and inferential analysis (SEM). The findings indicated that attitudes (general attitudes, personal attitudes, emotional values, and intelligence) and perceptions of behavioural control (experience, knowledge, media, and intervention), which in turn influence behaviour, are the primary contributors to farmers' behavioural intentions, which in turn influence farmers' actual behaviour. It is well established that farmers' behavioural intentions are unaffected by subjective norms, including age, gender, education level, income level, and religion. Farmers have started to be encouraged to try to work in groups through the formation of farmer groups and cooperatives as part of the process of fostering and developing oil palm. This is due to the fact that ISPO certification will only be given to farmers who are members of farmer groups or cooperatives. This is due to the fact that certification from ISPO will only be granted to farmers who satisfy the standards of both.